The Effectiveness of a Guided Internet-Based Tool for the Treatment of Depression and Anxiety in Pregnancy (MamaKits Online): Randomized Controlled Trial - Heller, Hanna M; Hoogendoorn, Adriaan W; Honig, Adriaan; Broekman, Birit F P; van Straten, Annemieke (JMIR Publications, 2020)
BackgroundPregnant women with symptoms of depression or anxiety often do not receive adequate treatment. In view of the high incidence of these symptoms in pregnancy and their impact on pregnancy outcomes, getting treatment is of the utmost importance. A guided internet self-help intervention may help to provide more women with appropriate treatment. ObjectiveThis study aimed to examine the effectiveness of a guided internet intervention (MamaKits online) for pregnant women with moderate to severe symptoms of anxiety or depression. Assessments took place before randomization (T0), post intervention (T1), at 36 weeks of pregnancy (T2), and 6 weeks postpartum (T3). We also explored effects on perinatal child outcomes 6 weeks postpartum. MethodsThis randomized controlled trial included pregnant women (<30 weeks) with depressive symptoms above threshold (ie, Center for Epidemiological Studies Depression scale [CES-D] >16) or anxiety above threshold (ie, Hospital Anxiety and Depression Scale-Anxiety subscale [HADS-A] >8) or both of them. Participants were recruited via general media and flyers in prenatal care waiting rooms or via obstetricians and midwives. After initial assessment, women were randomized to (1) MamaKits online in addition to treatment as usual or (2) treatment as usual (control condition). MamaKits online is a 5-week guided internet intervention based on problem solving treatment. Guidance was was provided by trained students pursuing a Master's in Psychology. Outcomes were based on a Web-based self-report. Women in the control condition were allowed to receive the intervention after the last assessment (6 weeks postpartum). ResultsOf the 159 included women, 79 were randomized to MamaKits online, 47% (79/37) of whom completed the intervention. Both groups showed a substantial decrease in affective symptoms on the CES-D, HADS-A, and Edinburgh Postnatal Depression Scale over time. In the intervention group, affective symptoms decreased more than that in the control group, but between-group effect sizes were small to medium (Cohen d at T3=0.45, 0.21, and 0.23 for the 3 questionnaires, respectively) and statistically not significant. Negative perinatal child outcomes did not differ between the 2 groups (χ21=0.1; P=.78). Completer analysis revealed no differences in outcome between the treatment completers and the control group. The trial was terminated early for reasons of futility based on the results of an interim analysis, which we performed because of inclusion problems. ConclusionsOur study did show a significant reduction in affective symptoms in both groups, but the differences in reduction of affective symptoms between the intervention and control groups were not significant. There were also no differences in perinatal child outcomes. Future research should examine for which women these interventions might be effective or if changes in the internet intervention might make the intervention more effective. Trial RegistrationNetherlands Trial Register NL4162; https://tinyurl.com/sdckjek